PENYELENGGARAAN RUPS MELALUI MEDIA ELEKTRONIK TERKAIT KEWAJIBAN NOTARIS MELEKATKAN SIDIK JARI PENGHADAP - Amelia Sri Kusuma Dewi (Arena Hukum, 2015)
AbstractThis research aims to analyze existing norms conflict between Article 16 Paragraph (1) c of Act No. 2 of 2014 on the Amendment Act No. 30 of 2004 concerning Notary which provides that the Notary required to attach the fingerprint of the parties facing the Minuta Deed, and Article 77 of Act No. 40 of 2007 on Limited Liability Company which provides that the Annual General Meeting of Shareholders (AGMS) through media teleconference, videoconference, or other means of electronic media. It also examines the juridical implications of the Notary and Acts of the AGMS through electronic media if the Notary does not fulfill the obligation to attach the fingerprint of the parties facing the Minuta Deed. To answer the above norm conflict, the type of research conducted by researchers is a normative juridical research using the statute approach and conceptual approach. The results of this research, that there is a conflict of norms in the form of obscurity norm, disharmony and emptiness norm in the relevant legislation. Regarding the juridical implications of the notary when not fulfilling the obligation to attach the fingerprint of the parties facing the Minuta Deed, then the notary may be subject to sanctions pursuant to Article 16, paragraph (11) of Act No. 2 of 2014 on the Amendment of Act No. 30 of 2004 on the Notary. As against the deed of the AGMS, fingerprint embedding function within minutes of notarial deed is not a legal action to determine the validity or authenticity of the certificate, but only serves to ensure the correctness identity of the facing parties.Â AbstrakPenelitian ini bertujuan menganalisa konflik norma yang ada antara Pasal 16 Ayat (1) huruf c Undang-undang Nomor 2 Tahun 2014 tentang Perubahan Undang-undang Nomor 30 tahun 2004 tentang Jabatan Notaris yang mengatur bahwa Notaris wajib untuk melekatkan sidik jari penghadap pada Minuta Akta, demikian dengan Pasal 77 Undang-undang Nomor 40 tahun 2007 tentang Perseroan Terbatas (UUPT) yang mengatur bahwa penyelenggaraan Rapat Umum Pemegang Saham (RUPS) melalui media telekonferensi, video konferensi, atau sarana media elektronik lainnya. Selain itu juga mengkaji implikasi yuridis terhadap Notaris dan akta RUPS melalui media elektronik apabila Notaris tidak memenuhi kewajiban untuk melekatkan sidik jari penghadap pada minuta akta. Untuk menjawab konflik norma tersebut di atas, jenis penelitian yang dilakukan oleh peneliti adalah penelitian yuridis normatif dengan menggunakan pendekatan statute approach (pendekatan perUndang-undangan) dan conceptual approach (pendekatan konsep). Hasil penelitian, bahwa terjadi konflik norma berupa kekaburan norma, disharmonisasi maupun kekosongan norma di dalam peraturan perUndang-undangan terkait. Mengenai implikasi yuridis terhadap Notaris apabila tidak memenuhi kewajiban untuk melekatkan sidik jari penghadap pada minuta akta, maka Notaris dapat dikenai sanksi sesuai pasal 16 ayat (11) Undang-undang Nomor 2 Tahun 2014 Tentang Perubahan Atas Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris. Sedangkan terhadap akta RUPS, fungsi melekatkan sidik jari dalam minuta akta Notaris bukan suatu tindakan hukum dalam menentukan keabsahan atau otentisitas dari akta tersebut melainkan hanya berfungsi untuk menjamin kebenaran identitas penghadap.Â